PENGARUH MOTIVASI TERHADAP PENINGKATAN PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR SAMSAT KABUPATEN SIDRAP - Sri Andayaningsih; Rulianty Rulianty (Jurnal Ilmu Manajemen Profitability, 2020)
The purpose of this study was to determine the effect of motivation on increasing employee productivity in the Samsat Sidrap District office. The research method uses quantitative methods because the research data are numbers that are processed using spss 20 alerts. With a population of 45 and a sample of 31 respondents the data analysis technique used in this study is simple linear regression with motivation variables (X) and employee performance (Y ). The results showed that from the simple linear regression that was processed and analyzed using the SPSS method, the equation obtained was Y = 6.592 + 0.664 X, where the constant number has a value of 6.592 (positive) stating that if there is no work motivation (X) then productivity work (Y) is 0.664, meaning that the employee's work productivity is still constant even though work motivation towards Y is zero. If there is a decrease in work motivation, it will reduce the level of employee productivity. So that it can be explained that work motivation has an influence and significant effect on employee work productivity in the Samsat district office